Australian Pharmacy Network : Learning Outcomes for Pharmacy Curriculum. - Stupans, Ieva (Office for Learning and Teaching, 2014)
The network will provide a focus for ongoing collaborative work in the discipline to address learning standards, embedding these in future academic practices, thus enhancing academic capacity across pharmacy schools and embedding and systematizing change through the focus on competency focused learning outcomes. Using collaborative workshops, student consultation and a system of university-based curriculum champions, comprehensive learning outcomes have been developed for the teaching of pharmacy in Australian universities. These outcomes, when built into the student learning experience, will make for competent, confident and work-ready pharmacy interns and graduates. Several Australian universities are actively incorporating the outcomes into their curriculum in 2014.